ANALISIS PERSEPSI KONSUMEN TERHADAP KUALITAS LAYANAN TRAVEL PO. KERINCI MULYA JAMBI - Dikky Alam M. (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2015)
This study aims to explain the analysis of consumer perceptions of the quality of PO travel services. Kerinci Mulya Jambi and to analyze consumer perceptions of the quality of PO travel services. Kerinci Mulya Jambi. The research method uses an average score. The results of the study concluded that based on the results of the average score obtained from each of the five dimensions of the variable, it indicated that PO travel customers. Kerinci Mulya Jambi in this study was satisfied with the quality of service provided by the travel PO. Kerinci Mulya. Of the five service dimensions measured, the reliability dimension, the responsiveness dimension, and the assurance dimension, the delivery of which is in line with the customer's perceived expectations of the services provided by the travel PO. Kerinci Mulya Jambi has not been optimally felt by these customers. It can be seen that the average consumer perception score is 4.18. It can be concluded that the level of quality of PO travel services. Kerinci Mulya Jambi is satisfying. On the Responsiveness service dimension related to responsiveness in more detail regarding the ability of employees to provide information, in this case the ability of bus crews to provide information and speed in serving goods delivery, customer expectations related to the ability of travel drivers to know more in-depth passenger pick-up routes again as well as the information needed by the recipient of the shipment of goods if the shipment has arrived it is expected as soon as possible to get information from the travel party to the customer having the lowest level of satisfaction among the five service dimensions measured.